Interpretative phenomenological analysis theory, method and research - Smith, Jonathan A.; Flowers, Paul.; Larkin, Michael 1971-. (Los Angeles, Calif. Sage Publications, 2009)
This title presents a comprehensive guide to interpretative phenomenological analysis (IPA) which is an increasingly popular approach to qualitative inquiry taught to undergraduate and postgraduate students today.
Keywords: Phenomenological psychology; Psychology -- Research; Qualitative Research